Enhanced chloroplastic generation of H2O2 in stress‐resistant Thellungiella salsuginea in comparison to Arabidopsis thaliana. Issue 3 (5th August 2014) - Wiciarz, Monika; Gubernator, Beata; Kruk, Jerzy; Niewiadomska, Ewa
<x xml:space="preserve">Abstract</x> In order to find some basis of salinity resistance in the chloroplastic metabolism, a halophytic Thellungiella salsuginea was compared with glycophytic Arabidopsis thaliana. In control T.s. plants the increased ratios of chlorophyll a/b and of fluorescence emission at 77 K (F730/F685) were documented, in comparison to A.t.. This was accompanied by a higher YII and lower NPQ (non‐photochemical quenching) values, and by a more active PSI (photosystem I). Another prominent feature of the photosynthetic electron transport (PET) in T.s. was the intensive production of H2O2 from PQ (plastoquinone) pool. Salinity treatment (0.15 and 0.30 M NaCl for A.t. and T.s., respectively) led to a decrease in ratios of chl a/b and F730/F685. In A.t., a salinity‐driven enhancement of YII and NPQ was found, in association with the stimulation of H2O2 production from PQ pool. In contrast, in salinity‐treated T.s., these variables were similar as in controls. The intensive H2O2 generation was accompanied by a high activity of PTOX (plastid terminal oxidase), whilst inhibition of this enzyme led to an increased H2O2 formation. It is hypothesized, that the intensive H2O2 generation from PQ pool might be an important element of stress preparedness in Thellungiella plants. In control T.s. plants, a higher activation state of carboxylase ribulose‐1, 5‐bisphosphate carboxylase/oxygenase (Rubisco, EC 4.1.1.39) was also documented in concert with the attachment of Rubisco activase (RCA) to the thylakoid membranes. It is supposed, that a closer contact of RCA with PSI in T.s. enables a more efficient Rubisco activation than in A.t.